Evaluasi dan Perbaikan Desain Antarmuka Pengguna Situs Web SMK Negeri 1 Bangsri dengan Menggunakan WEBUSE dan Human Centered Design - Bintang Fajrianti; Aditya Rachmadi; Fitra A. Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
SMK Negeri 1 Bangsri is a high school that has an official website as a media for education and also information about the school. Based on the results from the interview with users, several problems on the website interface of SMK Negeri 1 Bangsri were found which affect the usability of the website, such as poor navigation layout, unfamiliar menus naming, inappropriate colors, reading difficulties, even less informative information. Therefore, it is necessary to do evaluation and improvement on the website interface using Human Centered Design (HCD). In this research, evaluation processes are done using WEBUSE questionnaire so that improvement on the interface can be done better. The results of the usability evaluation for SMK Negeri 1 Bangsri official website on current design and prototype design show the increase in the value of usability. The results of the initial evaluation showed the website usability is in moderate level (range 0.4-0.6) and then turns to good level (range 0.6-0.8) on the final evaluation, with the increase on the Content, Organisation and Readability category from 0.65 to 0.76, Navigation and Links category from 0.57 to 0.72, User Interface Design category from 0.51 to 0.77, and Performance and Effectiveness category from 0.65 to 0.72.